Causes of Delay During Interfacility Transports of Injured Patients Transported by Air Ambulance. (2nd September 2020) - Nolan, Brodie; Haas, Barbara; Tien, Homer; Saskin, Refik; Nathens, Avery
Abstract: Background: Many severely injured patients are initially brought to a non-trauma centers for initial assessment and stabilization. Air ambulance services are commonly used to expedite interfacility transport of injured patients to trauma centers. Little is known of the types of delays experienced during interfacility transports. The purpose of this study was to identify specific causes of modifiable delays and estimate the attributable time associated with each of these delays. Methods: This was a retrospective cohort study of injured patients undergoing interfacility transfer to a trauma center who were transported by a provincial air ambulance service between January 1, 2014 and December 31, 2016. Electronic patient care records were screened and then manually reviewed to identify causes of delay during the interfacility transport process. The attributable time for each of these delays was also estimated. Results: There were 932 injured patients emergently transported by air ambulance from a community hospital to a trauma center over the 3-year study period from which 458 unique causes of delay that were identified. The most frequent cause of delays to sending facility were refueling (38%), waiting for land emergency medical services escort (25%) and weather (12%). The most common in-hospital delays included waiting for documentation (32%), delay to intubate (15%), medically unstable patient (13%) and waiting for diagnostic imaging (12%). The most frequent delays to receiving/handover included waiting for land EMS escort (31%), trauma team not assembled (24%) and weather (17%). In-hospital delays with the longest average length of delay included chest tube insertion (53 minutes), intubation (49 minutes) and delays for diagnostic imaging (46 minutes). Conclusions: In conclusion, we identified numerous modifiable causes of delay during interfacility transport. Efforts to reduce these delays can be made at both the air ambulance and hospital levels.